Surgical Management of Sublingual Mucocele (Ranula) in a Crossbreed Dog: A Case Study - Sonowal, Palash J.; S., Gokulraj; Debnath, Saurav; Deka, Champak; Islam, Sikder J. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
A mucocele is an accumulation of mucoid saliva in the submucosal or subcutaneous tissue due to a tear in asalivary gland capsule or duct (Bellenger and Simpson, 1992). The mucocele has a nonepithelial non-secretory linning,mainly consisting of connective tissues and capillaries (Karbe\ and Nielsen, 2008; William et al., 2008). The etiology of salivarymucocele is rarely identified (Boydell et al., 2000). Mucoceles are the most common salivary gland disorder of dogs butrarely occur in cats as well as in other species (Dunning, 2003). The most frequently involved salivary glands are the ducts ofsublingual and mandibular glands. The present case report describes ranula's diagnosis and surgical management in atwo years old male crossbred dog.